PERAWATAN DAN PELESTARIAN BAHAN PUSTAKA DI UNIT PELAKSANA TEKNIS PERPUSTAKAAN POLITEKNIK NEGERI SRIWIJAYA PALEMBANG - Agustin, Ita; Rohmaniyah, Rohmaniyah (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2023)
This research aims to reveal the extent to which the role of the Palembang community in maintaining traffic order in the local area. The research approach used is qualitative with a focus on literature review equipped with supporting data to support the content of the research results. This research aims to identify the influence of culture and social norms on traffic awareness in Indonesia. Values that support high traffic awareness, such as mutual respect, concern for shared safety, and individual responsibility, are important factors in shaping public awareness of traffic. In addition, this research also highlights the role of communities in shaping traffic awareness. Through community activities, such as safety campaigns, joint patrols, and participation in educational programs, people are actively involved in maintaining traffic order in their neighborhoods. Based on the results of the research, it can be said that the Palembang community still does not play an active role in the implementation of traffic order and is still dependent on what is done by the Palembang Police Traffic Unit itself.